HARVESTING POTENTIAL: UNVEILING THE AGRICULTURAL FRONTIER OF THE INTERNET OF UNDERGROUND THINGS - Mukhamedadiuly, Beksultan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
The Internet of Underground Things enhances precision agriculture by enabling real-time monitoring of soil conditions to improve sustainability and productivity. This project investigates signal propagation in underground environments, focusing on path loss and channel capacity as key performance metrics. Through MATLAB simulations replicating a reference experiment, the study analyzes the effects of distance, frequency, soil moisture, and sensor placement on signal attenuation and data rates. Comparative evaluations with established literature validate the findings, highlighting the sensitivity of path loss and capacity to soil moisture and the tradeoffs in frequency selection. Optimized sensor placement strategies are proposed to maximize communication efficiency. The results provide insights for designing robust IoUT systems, contributing to sustainable agricultural practices.
Keywords: Precision agriculture; Internet of Underground Things; Wireless underground sensor networks; Path loss; Channel capacity; type of access: open access